Lipid Exchangers: Cellular Functions and Mechanistic Links With Phosphoinositide Metabolism - Lipp, Nicolas-Frédéric; Ikhlef, Souade; Milanini, Julie; Drin, Guillaume (Frontiers in Cell and Developmental Biology, 2020)
Lipids are amphiphilic molecules that self-assemble to form biological membranes. Thousands of lipid species coexist in the cell and, once combined, define organelle identity. Due to recent progress in lipidomic analysis, we now know how lipid composition is finely tuned in different subcellular regions. Along with lipid synthesis, remodeling and flip-flop, lipid transfer is one of the active processes that regulates this intracellular lipid distribution. It is mediated by lipid transfer proteins (LTPs) that precisely move certain lipid species across the cytosol and between the organelles. A particular subset of LTPs from three families (Sec14, PITP, OSBP/ORP/Osh) act as lipid exchangers. A striking feature of these exchangers is that they use phosphatidylinositol or phosphoinositides (PIPs) as a lipid ligand and thereby have specific links with PIP metabolism and are thus able to both control the lipid composition of cellular membranes and their signaling capacity. As a result, they play pivotal roles in cellular processes such as vesicular trafficking and signal transduction at the plasma membrane. Recent data have shown that some PIPs are used as energy by lipid exchangers to generate lipid gradients between organelles. Here we describe the importance of lipid counter-exchange in the cell, its structural basis, and presumed links with pathologies.